APPLICATIONS AND INCLUSIVE ASPECTS OF ROBOTIC TECHNIQUES AND ARTIFICIAL INTELLIGENCE IN BIOLOGY EDUCATION - Salimova Sarvinoz Farkhodovna; Avezova Mukhayo Khasan kizi (American Journals, 2024)
Robotics and artificial intelligence (AI) are revolutionizing biology education by providing innovative tools and methods for teaching and learning. This paper explores how these technologies enhance educational experiences through interactive simulations and personalized learning platforms. Robotics allows students to engage with biological processes in a hands-on manner, while AI offers adaptive learning tailored to individual needs. Case studies demonstrate successful implementations, such as VR environments for exploring cellular structures and AI-driven tutoring systems.
Keywords: Robotics, artificial intelligence (AI), biology education, interactive learning methods, inclusivity, educational technologies, personalized learning, virtual laboratories, AI-based learning platforms, future trends.